Restoring the Scientific Potential of Ukrainian Science: Necessity and Real Prospects - Popovych, O.S.; Kostrytsa, O.P. (Science and Innovation, 2024)
The urgent necessity of restoring the human potential of Ukrainian science has been substantiated. A method for forecasting the evolution of human capacity of science has been developed based on consideration of the relationship and interdependence of adjacent age groups of scientists. The possible options for human capacity recovery in Ukraine have been estimated for two decades. Provided the recent trends remain fixed, the number of researchers by 2035 has been showed to decrease 4.5 times as compared with 2015, unless the government cardinally changes the attitude towards science. At the same time, even if significantly increasing salary and improving working conditions of researchers lead to a 25 % growth in the inflow of young researchers to science every 5 years and provided the number of researchers over 30 years who leave the R&D sector does not exceed 1%, at best, it will enable to stabilize the human potential of Ukrainian science, but is still not enough to essentially enlarge it. The option of stimulating a 40% increase in the inflow of young researchers is also not sufficient. Only the implementation of measures that would ensure doubling inflow of young researchers every 5 years can give an opportunity to reach by 2035 the number of researchers close to that in the early 1990s, i.e. to get their ratio per 1 million comparable to the EU countries. Moreover, it is necessary to start implementing this policy immediately: if it is postponed until 2020, such an accelerated rate of escalating the arrival of young people in science will not enable to reach in 20 years the number of researchers Ukraine had in the not-so-successful 2010.